Hematological markers and biochemical profiles in terms of gender and age of captive collared peccaries (Tayassu tajacu) in eastern Amazon - Jorge, E. M.; Silva, C. J. O.; Ritter, R. A.; Monteiro, M. V. B.; Albuquerque, N. I.; Kahwage, P. R.; Monteiro, F. O. B.; Costa, C. T. C.; Rahal, S. C. [UNESP]; Silva Filho, E. (Funpec-editora, 2015)
Complete blood counts and blood biochemical analyses are laboratory tests that allow the monitoring of physiological condition, nutrition, and health in free-living or captive wild animals. When interpreting these tests, it is essential to compare the results with reference ranges that are suitable for the species. Few studies have been conducted on the hematological and biochemical characteristics of Tayassu tajacu, particularly for animals raised in the Amazon biome. The objectives of this study were to evaluate the influence of age and gender on the hematological and biochemical profiles of captive T. tajacu, and to establish reference intervals for these parameters. Complete blood counts and biochemical analyses were performed using manual methods and semi-automatic equipment, respectively. There were significant differences in relation to age in hematocrit and hemoglobin levels, and mean cell volumes, in captive T. tajacu. No basophils were observed, and the neutrophil: lymphocyte ratio was less than 1. Levels of total protein, urea, phosphorus, and alkaline phosphatase were significantly affected by age (P < 0.05). Gender did not affect any of the results. The hematological and biochemical parameters for this species were determined, and may be used as reference ranges for captive T. tajacu.
Keywords: Reference interval; Complete blood count; Leukogram; Tayassuidae